1971
DOI: 10.1172/jci106566
|View full text |Cite
|
Sign up to set email alerts
|

The effect of administration of human growth hormone on the plasma growth hormone, cortisol, glucose, and free fatty acid response to insulin: evidence for growth hormone autoregulation in man

Abstract: A B S T R A C T The effect of administration of human growth hormone (HGH) (3 mg every 6 hr for 6 days) on the endogenous GH response to insulin-induced hypoglycemia at 8, 12, 24, and 48 hr posttreatment was studied in 11 healthy male adults. Free fatty acid, cortisol, and glucose responses pre-and posttreatment with HGH were evaluated concurrently. Control subjects received saline injections to evaluate relationship of GH responses to the periodicity of insulin tolerance tests. The data were compared for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
5

Year Published

1973
1973
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(36 citation statements)
references
References 39 publications
2
28
1
5
Order By: Relevance
“…A pharmacologic dose of GH was used since we found in a previous study that a comparable dose inhibited the rise in the concentration of plasma GH elicited by insulin-induced hypoglycemia (9). Despite the pharmacologic dose ofGH in the current study, plasma GH levels had fallen to the 2-4 ng/ml range in all patients by 12 h after the final GH injection, at which time GRF was given (Fig.…”
Section: In Vivomentioning
confidence: 61%
See 1 more Smart Citation
“…A pharmacologic dose of GH was used since we found in a previous study that a comparable dose inhibited the rise in the concentration of plasma GH elicited by insulin-induced hypoglycemia (9). Despite the pharmacologic dose ofGH in the current study, plasma GH levels had fallen to the 2-4 ng/ml range in all patients by 12 h after the final GH injection, at which time GRF was given (Fig.…”
Section: In Vivomentioning
confidence: 61%
“…Previous studies from this laboratory and by others in rats, monkeys, and humans support the concept that growth hormone (GH)' can regulate its own secretion through an autofeedback mechanism (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Such studies demonstrated that exogenous GH either led to diminished pituitary GH content (1)(2)(3)(4)(5)(6), blunted the GH response to provocative stimuli (7-10), or decreased 1. Abbreviations used in this paper: GH, growth hormone; SRIF, somatotropin-release inhibiting factor (somatostatin); GRF, GH-releasing factor; SM-C, somatomedin-C.…”
Section: Introductionmentioning
confidence: 87%
“…The absence of such centers in alnencephaly would, of course, preclude such a control system. Autoregulation of growth hormone secretion by growth hormone itself, another postulated mechanism for growth hormone control (33,34), would also be interfered with if the sensor is in the hypothalamus. (25).…”
Section: Resultsmentioning
confidence: 99%
“…Refractoriness of GH secretion to repeated stimulation by L-dopa (22) or sequential exercise and arginine infusion (23) has been previously demonstrated. Furthermore, exogenous GH administration inhibits spontaneous pulsatile endogenous GH secretion in the rat (24) and inhibits nyctohemeral (25) and insulin- (26), arginine-, or exercise-induced (23) GH secretion in man by unknown but possibly somatostatin-mediated mechanisms. GH stimulates somatostatin release from the rat hypothalamus in vitro within 20 min at a concentration of 20 ng/ ml (8).…”
Section: Discussionmentioning
confidence: 99%